The Role of Islam in Shaping the Idea of Indonesia - Imanuddin Abil Fida; Benny Prasetiya (AJIS: Academic Journal of Islamic Studies, 2019)
This study will describe information that Islam plays a role in influencing the struggle in determining the main ideology of the Indonesian people. Some Indonesian Muslim leaders strive to determine the foundation of the country in studying Indonesian history requires a proper understanding of the role of Islam. Before independence, the movement of Islam in Indonesia was divided into two major currents: traditionalists who developed in the countryside and modernists who grew up in urban areas. The current type of research is critical analysis. This research is based on library research and textual analysis of relevant materials taken from primary and secondary sources on history, development, change and transformation. The results of this study reveal that nationalism does not conflict with Islam and therefore Muslims can apply it in their lives. This is because nationalism can be used to obtain peace among the people whether they are Muslim or non-Muslim. Nationalism will not harm Islam and Muslims in Indonesia because nationalism is part of Islam. They allow the application of man-made laws such as nationalism as long as they are suitable for Muslims. However, their acceptance of Pancasila as a state ideology is a reflection of their commitment to Indonesian nationalism.